Hierarchical 3D TiO2 Nanotube Arrays Sensitized by Graphene Oxide and ZnxCdyS for High Performance Photoelectrochemical Applications. Issue 24 (13th November 2018) - Bao, Ruiyu; Geng, Junfeng; Sullivan, James A.; Xia, Jianxin; Wang, Wenzhong; Wong, Wai‐Yeung; Li, Hua
Abstract : Photocatalysis and photoelectrocatalysis are highly promising for applications in the energy and environment sectors. Several photocatalytic devices based on TiO2 nanotubes grown on two‐dimensional (2D) substrate (such as titanium foil) have been developed, but there has been little research on three‐dimensional (3D) TiO2 nanotubes which are expected to offer significantly enlarged surface area and much improved photocatalytic efficiency. Here, a method of building 3D TiO2 nanotube arrays (3D‐TNTAs) on titanium mesh by anodization via controlling the reaction time and electrolyte is reported. It is found that the electrochemically active area of such a titanium mesh is almost 4 times larger than that of the traditional titanium foil. Moreover, through making composites of graphene oxide and Zn x Cd y S onto 3D TiO2 nanotubes, hierarchical nanotube arrays (Zn x Cd y S/GO/3D‐TNTAs) are made by calcination‐deposition of graphene oxide followed by a facile successive ionic layer adsorption reaction (SILAR) treatment with Zn x Cd y S. Characterization of the Zn x Cd y S/GO/3D‐TNTAs indicates that this hierarchical multi‐layered nanostructure has a much improved photoelectrochemical property due to the enlarged surface area and improved electron–hole separation capability, demonstrating the great potential for applications in photoelectrocatalytic devices for environmental technologies. Abstract : Through making composites of graphene oxide and Zn x Cd y S onto 3D TiO2 nanotubes, hierarchical nanotube arrays (Zn x Cd y S/GO/3D‐TNTAs) are made by calcination‐deposition of graphene oxide followed by a facile successive ionic layer adsorption reaction treatment with Zn x Cd y S. The Zn x Cd y S/GO/3D‐TNTAs (12 deposition cycles) reach the highest steady photocurrent density, which is roughly 10 times that of the non‐sensitized 3D‐TNTAs under identical testing conditions.